Knowledge dialogue: from useful agrobiodiversity towards the construction of medicinal knowledge (Zautla, Mexico) - De la Fuente Garnica, Pablo; Navarro, Alonso Gutiérrez (Agrociencia Uruguay, 2022)
The dialogue of knowledge is a horizon for agroecology in political, epistemic, ethical dimensions and gives the possibility of building alternatives to the production of hegemonic knowledge. In addition, it allows us to question the object of knowledge of ethnosciences. The article presented here reconfigures more than 20 years of work experience of the Center for Rural Development Studies (CESDER) with peasant and indigenous community groups in Zautla, Mexico. The methodology arises from the collection and taxonomic determination of plant collections in the area, which serve as a basis for the verification of uses and common names through semi-structured interviews, and in the end, can trigger exchanges and dialogues with community groups through the herbarium specimens with emphasis on medicinal use. The results indicate that the condensation of the material and the symbolic makes life stories, memories, anecdotes, uses, recipes, experiences, and valuations emerge, and achieves the sharing of what is essential for cultural appropriation. For us, the conclusions go beyond the convergence in taxonomic identification and common names since they lead to changes in practices in daily life, generate knowledge from dialogue, and reproduce moments in which coexistence, sharing, life stories related to their experience emerge. The approach to a dialogue of knowledge arises from the constancy of the space being always under construction and the consequent exchange.